IDENTIFIKASI DAN MITIGASI PENYEBAB BUTIRAN STEARIN DAN CLOUDY PADA PRODUK OLEIN MENGGUNAKAN PENDEKATAN FAILURE MODE AND EFFECT ANALYSIS (FMEA) UNTUK OPTIMALISASI PROSES PRODUKSI MINYAK GORENG DI PT. XYZ - Akbar Gustawa ,; Masdania Zuraiah Siregar ,; Rizka Ridha , (Journal of Innovation Research and Knowledge, 2026)
Increasingly tight business competition requires every company to produce products with good and high quality. This is also not out of the view of PT. XYZ, which is one of the large companies that processes products from palm oil and its derivatives, one of which is cooking oil. Now cooking oil is easily found on the market with various brands. Tight competition and maintaining product quality are things that are very mandatory for PT. XYZ so that consumers continue to use the product. In the cooking oil products produced, there are several findings of product defects, namely stearin and cloudy grains. This causes losses for the company, so a control method is needed to minimize the occurrence of product defects. One of the methods used is the Failure Mode and Effect Analysis (FMEA) method, which is a technique used to improve the reliability and safety of a process by identifying failures or failure modes in a production process. This study is also expected to provide suggestions for improvements for PT. XYZ in minimizing product defects. The results obtained are the highest RPN value for defective products due to stearin granules of 504, which is caused by the clamping ring to bind the clouth filter being loose / damaged, so that the stearin granules escape from the small gap of the clamping ring. And the RPN value for defective products due to cloudy is 252, which is caused by a torn / leaking Clouth Filter. The proposed improvement is to tighten and check the clamping ring once an hour, to tighten and check the Clouth Filter periodically, which is once a month. And flush the line using nitrogen gas and ensure that each valve is not damaged / passing. And the proposed improvements using the 5W+1H tools are to replace the clamping ring periodically, Conduct SOP training on the installation of the clamping ring and filter cloth, Conduct a visual checklist on the product before it is sent to the product tank.